ATPase activity of GroEL is dependent on GroES and it is response for environmental stress in Riemerella anatipestifer. (August 2018) - Liu, Jibin; Wang, Mingshu; Yi, Haibo; Liu, Mafeng; Zhu, Dekang; Wu, Ying; Jia, Renyong; Sun, Kunfeng; Yang, Qiao; Chen, Shun; Zhao, Xinxin; Chen, Xiaoyue; et al.
Abstract: Riemerella anatipestifer (Ra) is a serious gram-negative pathogen of birds and can cause considerable economic losses. The survival mechanisms of R. anatipestifer in the host and environment remain largely unknown. Previous results have demonstrated that GroEL is a molecular chaperone and an important component of the response to various stresses in most bacteria. This study focused on whether GroEL is implicated in this process in R. anatipestifer . The 1629 bp groEL is highly conserved among other gram-negative bacteria (levels of sequence similarity > 60%). A structural analysis and ATPase activity assay revealed that Ra GroEL had weak ATPase activity and that the enzyme activity was temperature and ion dependent. GroES partially enhanced the GroEL ATPase activity in the same temperature range. In addition, we studied the mRNA expression of groEL under abiotic stresses caused by heat shock, pH, salt and hydrogen peroxide. These stresses increased the transcription of groEL to varying degrees. In R. anatipestifer, the ATPase activity of GroEL is dependent on GroES and temperature. The expression of groEL was strongly induced by heat, pH, hydrogen peroxide and salt stress. This study is the first to show that GroEL in R. anatipestifer might play a major role in response to environmental stress. Highlights: The 3-dimensional structure of Ra GroEL was first determined by homology modelling. Ra GroEL has weak ATPase activity and is temperature and ion dependent. gro EL and gro ES are transcribed as a single operon in R. anatipestifer. gro EL in R. anatipestifer is involved in various stress response.